Offering Decision of Risk-Based Wind-Photovoltaic-Thermal GenCo Using Downside Risk Constraints Approach - Peng Liu; Jinfeng Wang; Sayyad Nojavan; Kittisak Jermsittiparsert (IEEE Access, 2020)
Risk analysis and scheduling of a Generation Company (GenCo) under uncertain environments are challenging issues. So, stochastic optimization and downside risk constraints approaches are used in this paper to model and manage the risk associated with various uncertainties. The presented GenCo model comprised five thermal units, photovoltaic systems, and wind farms. It is assumed that all thermal units, photovoltaic systems, and wind farms can participate in the energy market. In contrast, only thermal units can participate in the reserve market. The uncertainty of electricity and reserve market prices and output power of photovoltaic systems and wind farms are modeled via a stochastic optimization approach. Afterward, the downside risk constraints method is used to manage the risks associated with various uncertainties. By analyzing the obtained results, it can be seen that the level of the average risk can plunge to 0 by gaining 4.68% less average profit. So, the GenCo can be immune against considered uncertainties with gaining a little bit less profit. Furthermore, the offering strategy is studied in two risk-neutral and risk-averse strategies. Finally, the CPLEX solver of GAMS software is used to optimize the studied linear-based model of GenCo.